Reassessment Of Performance Management System Towards Employee Productivity During The Pandemic Of Covid-19 In A Private Sector - Nurul Nerina, Mohamad Nor Adam (Universiti Malaysia Sarawak, (UNIMAS), 2021)
During the pandemic of Covid-19, there are many small business and organisation that fail to thrive and develop their growth because of loss of profit. The government has suggested for all employer to reassess their PMS as it could help company to achieve its goals and build resilience after the outbreak of Covid-19. Therefore, a qualitative study is conducted to explore the importance of reassessment of PMS towards employee’s productivity along of this pandemic. 7 informants were interviewed in order to get the data. This study focuses on the importance of PMS, ways to increase employee’s productivity, ways to cope with new normal and strategies to strengthen PMS. The result obtain from this study shows that by setting a clear objective, increase motivation, sharpen skills and reduce cost variance could help the company to thrive from this pandemic and measure employee’s performance. Also, this study shows that employee’s performance is not majorly affected by the pandemic where only 10% of the employees fail to reach their target. Therefore, the strategies have been stated in this report regarding this issues. The findings from this study may provide useful information and body of knowledge for both practitioners and future researcher for the purpose of helping organization to thrive during this pandemic.